Penerapan Artificial Intelligence (AI) Untuk Optimasi Jadwal Produksi Di Industri Manufaktur Dalam Upaya Meningkatkan Produktivitas Kerja - Agra Nurtrihadi; Jupriyanto; Dangan Waluyo (Penerbit Jurnal Indonesia, 2025)
Artificial Intelligence (AI) serves as a strategic solution capable of optimizing production schedules and significantly enhancing work productivity. The objectives of this study are to understand how Artificial Intelligence (AI) can optimize production scheduling in the manufacturing industry, identify the factors influencing the success of AI implementation in the production scheduling process, and determine the impact of AI implementation on work productivity in the manufacturing industry. The research method employed is qualitative. The findings of this study indicate that the implementation of AI provides efficiency, flexibility, and competitive advantages for the manufacturing industry. With the right strategies, this technology can achieve higher productivity, enhance company competitiveness, and support sustainable growth in the modern industrial era.